GeneGIS: Geoanalytical Tools and Arc Marine Customization for Individual‐Based Genetic Records. Issue 3 (June 2014) - Dick, Dorothy M.; Walbridge, Shaun; Wright, Dawn J.; Calambokidis, John; Falcone, Erin A.; Steel, Debbie; Follett, Tomas; Holmberg, Jason; Baker, C. Scott
Abstract To improve understanding of population structure, ecosystem relationships and predictive models of human impact in cetaceans and other marine megafauna, we developed geneGIS, a suite of GIS tools and a customized Arc Marine data model to facilitate visual exploration and spatial analyses of individual‐based records from DNA profiles and photo‐identification records. We used the open source programming language Python 2.7 and ArcGIS 10.1 software to create a user‐friendly, menu‐driven toolbar linked to a Python Toolbox containing customized geoprocessing scripts. For ease of sharing and installation, we compiled the geneGIS program into an ArcGIS Python Add‐In, freely available for download from the website http://genegis.org. We used the Lord‐Castillo et al. (2009) Arc Marine data model customization as the starting point for our work and retained nine key base Arc Marine classes. We demonstrate the utility of geneGIS using an integrated database of more than 18, 000 records of humpback whales (Megaptera novaeangliae) in the North Pacific collected during the Structure of Populations, Levels of Abundance and Status of Humpback Whales in the North Pacific (SPLASH) program. These records represent more than 8, 000 naturally marked individuals and 2, 700 associated DNA profiles, including 10 biparentally inherited microsatellite loci, maternally inherited mitochondrial DNA, and genetic sex.